Centers and peripheries in the public memory and the research of the Holocaust - Decheva, Daniela (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The paper examines the current transnational discourse on the Holocaust (policies, public memory, research) through the concept of center and periphery in two aspects: a) in regard to national societies; b) in regard to historical content. National contexts representative of the center and of various degrees of the periphery are considered. Thе analysis leads to the conclusion that targeted political measures in recent decades have established Holocaust memory and research as a filter for self-analysis of European national societies, as an indicator of the level of their democracy and even of their foreign policy positioning.
Keywords: center; periphery; Holocaust; memory politics; memory culture